Temperature and humidity conditions of Macocha Abyss - LITSCHMANN, Tomáš; ROŽNOVSKÝ, Jaroslav; STŘEDA, Tomáš; STŘEDOVÁ, Hana; HEBELKA, Jiří (Contributions to Geophysics and Geodesy, 2012)
The paper deals with the evaluation of temperature and humidity measurements in the vertical profile of Macocha Abyss (Moravian Karst, South Moravia, Czech Republic). The measuring profile on a rock wall is made up of seven HOBO-PRO sensors. Two other meteorological stations are installed at the bottom and near the upper edge of the abyss. The evaluation was designed separately for warm season (June 1, 2008 to August 31, 2008) and cold season (November 1, 2008 to February 28, 2009). In the warm season, distribution of inverse temperatures dominated in the abyss. Temperature differences between the bottom of the abyss and its upper edge reached about 10 °C. At the bottom of the abyss, the minimum temperatures proved to be higher than at its upper edge and in its vicinity. Thermal circulation is evident to the depth of about 60 m. The highest temperatures were observed in the deeper layers of the abyss in the warm period at around 10 a.m. of Central European Summer Time. Towards the upper edge of the abyss, the hour of daily maximum temperature shifts to 2 to 4 p.m. In the cold season, the minimum temperature was observed between 6 and 7 a.m. of Central European Time. A decrease in the accumulation of cold air (cold-air pool formation) was not found in the lower floors of the abyss. This phenomenon does not occur even during clear nights. The depth of 60 m from the upper edge of the area maintains a high relative humidity (above 95%) in the warm season. However, humidity decreases from this depth towards the top of the abyss. In the cold season, the whole abyss is filled with air with relative humidity of 90 to 95%.